PENGARUH PENERAPAN STRATEGI THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA - Ekaputri, Yanti Nazmai; Syafti, Okviani; Veni, Veni; Rahman, Antoni; Mayeni, Riska (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
The reality that occurs shows that students' mathematics learning achievement has not been in line with expectations. Students' mathematics learning outcomes based on test scores, there are still many students whose scores are below the specified KKM, which is 77. If you pay attention when learning takes place, it seems that many students are less interested in learning mathematics. Especially if the math class is at the last hour. This is one of the obstacles students are not motivated to learn mathematics. In addition, learning activities have not optimized student-centered learning models, so that the learning process feels less interesting so that students' understanding of mathematical concepts is still low. This study aims to determine the effect of the TTW strategy in improving learning outcomes in terms of understanding students' mathematical concepts. This type of research is a quasi-experimental research (quasi-experimental). The population in this study were students of class XI SMAN 1 Painan, class XI IIS 4 as the experimental class and class XI IIS 1 as the control class. The instrument used is a concept understanding test. The results of the hypothesis in this study are that students' understanding of mathematical concepts who take part in learning using the TTW type cooperative learning model is higher than students who use conventional learning. This means that the TTW type cooperative learning model has a good effect on students' conceptual understanding.